Morphology of Serous Retinal Detachment in Morning Glory Optic Disc Anomaly in a Patient before and after Treatment with Systemic Carboanhydrase Inhibitors - Sinner, Veronika; Valmaggia, Christophe; Todorova, Margarita (Klinische Monatsblätter für Augenheilkunde, 2023)
Background Morning glory optic disc anomaly (MGODA) is a rare congenital defect of the optic nerve head. The optic nerve is enlarged, and its conical excavation is filled with glial tissue. It may be associated with cerebral malformations and ocular complications, whereas serous retinal detachment occurs in 38% of affected patients. Surgical treatment of detachment showed poor visual outcome in the past and conservative treatment options are scarce.Case A woman with MGODA presented in our clinic with sudden vision loss due to serous retinal detachment. She denied any previous ophthalmological problems and her past medical history was unremarkable. Vision testing showed normal visual acuity in her left eye and finger counting in her right eye. Slit lamp examination was unremarkable. Fundus examination of the right eye showed retinal detachment without holes or traction membranes and an enlarged optic disc with raised peripapillary tissue and glial tissue in the center of the optic disc. Due to the pathognomonic otpic disc finding, we diagnosed MGODA complicated by a serous retinal detachment. We treated the patient with systemic carboanhydrase inhibitors and documented the initial clinical findings as well as the course of disease under treatment by optical coherent tomography (OCT), fundus autofluorescence imaging (FAF), and visual field testing. During follow-up, we detected noticeable subretinal fluid regression and improvement in visual acuity.Conclusion The application of oral carboanhydrase inhibitors appears to be a valid therapeutic option in patients with MGODA-associated serous macular detachment. OCT and FAF imaging are useful modalities for documentation of subretinal fluid regression and structural changes in the peripapillary region.
Keywords: neuroophthalmology; anatomy; retina